Validity of UPREP liquid based cytology in FNAC examination for palpable lesions type of article – original article - Dr. Bindhuja J; Dr. Jeyachadran Aswathy (Tropical Journal of Pathology and Microbiology, 2019)
Background: Liquid-based cytology (LBC) is a technique that enables cells to be suspended in a monolayer, through which better morphological assessment is possible. There are very few studies done to evaluate the outcomes between conventional and UPREP LBC method. A successful validation of UPREP LBC will go a long way in providing both affordable and accurate management of cancers in developing countries.Methods: This study was carried out as a comparative study among 110 all adults who were advised to undergo Fine Needle Aspiration Cytology (FNAC) examination for palpable lesions in thyroid, breast and lymph node in our tertiary care hospital. Conventional FNAC was taken for 55 participants and for the UPREP LBC group (55 participants), the same procedure was repeated and instead of air, preservative solution was drawn into the syringe. Various cytological parameters including cellularity, background, monolayer, cellular morphologic change, nuclear changes and inflammatory infiltrate were studied.Results: Among the individual lesions involving breast, thyroid and lymph node, breast carcinoma was highest in both the groups (25.4%) followed by fibroadenoma of the breast (20%) and Hashimoto’s thyroiditis (18.2%). Statistically significant differences were observed between the conventional and UPREP groups. Informative background was increasingly better in the conventional group compared to the UPREP group (p<0.001) while background debris was absent in most of the patients in UPREP group (p<0.001). Details pertaining to nucleus and cytoplasm were better perceived in the UPREP group compared to the conventional group (p<0.001).Conclusion: Manual liquid based cytology like UPREP LBC is an accurate, less expensive alternative procedure to automated LBC with the advantage of providing monolayer, absence of obscuring blood or debris, better nuclear and cytoplasmic morphology.